2022
DOI: 10.1002/ar.25120
|View full text |Cite
|
Sign up to set email alerts
|

Altered upper limb motor behavior in breast cancer survivors and its relation to pain: A narrative review

Abstract: Breast cancer is the most commonly diagnosed cancer among women and many women suffer from persistent physical and psychological complaints following their cancer treatment. Altered motor behavior at the shoulder region and upper limb, that is, alterations in movement patterns, spatiotemporal movement characteristics and muscle activation patterns, is a common physical consequence of breast cancer treatment, that can have a clear impact on daily life functioning and quality of life. Furthermore, altered upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Post-surgery pain severity 1.9 ± 1.0 1 Standard deviation. 2 Disability of Arm, Shoulder, and Hand questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Post-surgery pain severity 1.9 ± 1.0 1 Standard deviation. 2 Disability of Arm, Shoulder, and Hand questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer is the most common cancer among women [ 1 ]. Although survival rates are high, many women experience persistent physical problems following treatment [ 2 , 3 , 4 ]. These involve upper-limb (UL) problems (e.g., movement alterations; strength deficits; and altered sensations and pain in the arm, hand, and shoulder), all negatively affecting UL functionality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both in research and clinical practice, there is no doubt about the change in soft tissue properties due to breast cancer treatments. In the first paper (De Baets et al, 2024), an overview of the reported alterations in motor behavior at the level of the shoulder and upper limb in breast cancer survivors is provided, in combination with the known biopsychosocial mechanisms underlying such altered motor behavior.…”
Section: Introductionmentioning
confidence: 99%